Acid‐Promoted Chemoselective Introduction of Amide Functionality onto Aromatic Compounds Mediated by an Isocyanate Cation Generated from Carbamate. Issue 10 (19th August 2014) - Sumita, Akinari; Kurouchi, Hiroaki; Otani, Yuko; Ohwada, Tomohiko
Abstract Carbamates have been used as precursors of isocyanates, but heating in the presence of strong acids is required because cleavage of the CO bond in carbamates is energy‐demanding even in acid media. Direct amidation of aromatic compounds by isocyanate cations generated at room temperature from carbamoyl salicylates in trifluoromethanesulfonic acid (TfOH) was examined. Carbamates with ortho‐salicylate as an ether group (carbamoyl salicylates) showed dramatically accelerated OC bond dissociation in TfOH, which resulted in facile generation of the isocyanate cation. These chemoselective intermolecular aromatic amidation reactions proceeded even at room temperature and showed good compatibility with other electrophilic functionalities and high discrimination between N‐monosubstituted carbamate and N, N‐disubstituted carbamate. The reaction rates of secondary and tertiary amide formation were markedly different, and this difference was utilized to achieve successive (tandem) amidation reactions of molecules with an N‐monosubstituted carbamate and an N, N‐disubstituted carbamate with two kinds of aromatic compounds.